2014
DOI: 10.4212/cjhp.v67i3.1358
|View full text |Cite
|
Sign up to set email alerts
|

Time to Administration of Antibiotics among Inpatients with Severe Sepsis or Septic Shock

Abstract: Background: Current evidence suggests that administration of appropriate antibiotic therapy within 1 h after the onset of hypotension significantly improves mortality rates among patients with severe sepsis and septic shock.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 20 publications
2
31
0
Order By: Relevance
“…The timely administration of antibiotics is particularly important. The mortality rate from severe sepsis approaches 35 per cent, and several studies have demonstrated a survival benefit for patients treated with empirical antibiotics within 1 h of diagnosis. Although three‐quarters of patients were given antibiotics, only one‐third were delivered within 1 h of diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…The timely administration of antibiotics is particularly important. The mortality rate from severe sepsis approaches 35 per cent, and several studies have demonstrated a survival benefit for patients treated with empirical antibiotics within 1 h of diagnosis. Although three‐quarters of patients were given antibiotics, only one‐third were delivered within 1 h of diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Data for the 11 studies were developed between 2005 and 2013 with subsequent publication dates ranging from 2009 to 2016 (see Table 1). The trials were conducted in various countries: five in USA (including one multi-continent study including Europe) 6,[22][23][24][25] , one included a broad grouping 'Europe' 26 , and one each in Korea 27 , Canada 28 , The Netherlands 29 , Australia 30 and Iran 31 (see Table 1). The population of each study varied and included SIRS, sepsis, severe sepsis and septic shock.…”
Section: Resultsmentioning
confidence: 99%
“…13 In patients with severe sepsis and septic shock, prompt treatment of infection is the cornerstone of therapy and predictive of survival. 10 To select the right antimicrobial for the offending pathogen, knowledge of the causative organisms and their local antimicrobial susceptibility patterns is pivotal. In the present study, the vast majority of isolates were Escherichia coli, Klebsiella pneumoniae and Pseudomonas aeruginosa.…”
Section: Discussionmentioning
confidence: 99%
“…2,[6][7] Sepsis, resulting due to impairment of host defences to infection, [8][9] requires prompt implementation of antibiotic therapy to reduce morbidity and mortality. 10 Epidemiological studies have reported an increase in the incidence of severe sepsis and septic shock [11][12] with even gram positive and fungal organisms being the causative agents. 13 Thus, it is essential to have knowledge about the local epidemiological pat tern among the severe sepsis and septic shock patients since the organisms causing sepsis may not only vary based on regions but also change over time.…”
Section: Introductionmentioning
confidence: 99%